E-commerce implementation at the National Library Board, Singapore. - Chong, Alan Kim Meng. (2008)
The intent of this dessertation is to focus primarily on the phase 1 implementation of the E-Commerce Infrastructure to support the NAtional Library Board Digital Library initiative.